Naringin: Nanotechnological Strategies for Potential Pharmaceutical Applications - Soledad Ravetti; Ariel G. Garro; Agustina Gaitán; Mariano Murature; Mariela Galiano; Sofía G. Brignone; Santiago D. Palma (MDPI AG, 2023)
Polyphenols comprise a number of natural substances, such as flavonoids, that show interesting biological effects. Among these substances is naringin, a naturally occurring flavanone glycoside found in citrus fruits and Chinese medicinal herbs. Several studies have shown that naringin has numerous biological properties, including cardioprotective, cholesterol-lowering, anti-Alzheimer's, nephroprotective, antiageing, antihyperglycemic, antiosteoporotic and gastroprotective, anti-inflammatory, antioxidant, antiapoptotic, anticancer and antiulcer effects. Despite its multiple benefits, the clinical application of naringin is severely restricted due to its susceptibility to oxidation, poor water solubility, and dissolution rate. In addition, naringin shows instability at acidic pH, is enzymatically metabolized by β-glycosidase in the stomach and is degraded in the bloodstream when administered intravenously. These limitations, however, have been overcome thanks to the development of naringin nanoformulations. This review summarizes recent research carried out on strategies designed to improve naringin's bioactivity for potential therapeutic applications.